Mixed-methods evaluation of family medicine research training and peer mentorship in Lesotho - Chelsea M. McGuire; Katherine Riffenburg; Sebaka Malope; Brian Jack; Christina P.C. Borba (AOSIS, 2020)
Background: Strengthening primary care research capacity is a priority globally. Family medicine training programmes in sub-Saharan Africa represent an important opportunity to build primary care research; however, they are often limited by insufficient research training and mentorship. Peers can be used to extend research mentorship capacity, but have not been evaluated in this context. Aim: The aim of this study was to evaluate one family medicine training programme's research capacity building efforts through a blended research curriculum and peer mentorship. Setting: Lesotho is a landlocked country within South Africa of approximately two million people. The Family Medicine Specialty Training Programme (FMSTP) is the only accredited postgraduate medical education programme in Lesotho. Methods: This two-year mixed-methods evaluation used: (1) Likert-scale surveys measuring trainee research confidence, (2) written evaluations by trainees, peers, programme faculty and administrators and (3) in-depth, semi-structured interviews. Survey data were analysed using Friedman and sign tests. Interview and written data were analysed thematically via a mixed inductive-deductive approach using Cooke's framework. Results: Family Medicine Specialty Training Programme trainees (n = 8) experienced moderate increases in research confidence that were statistically significant. Skill-building occurred primarily via experiential learning. Research was grounded in trainees' clinical practice and locally relevant. A positive research culture was created, promising for sustainability. We identified infrastructure gaps, including funding and protected time. Peer research mentorship supported trainees' motivation and provided a safe space for questions. Conclusion: The FMSTP research curriculum and peer mentorship programme were successful in positively impacting a number of Cooke's research capacity domains. This evaluation identified improvements that are now being implemented.